Development of speech culture in Russian lessons - Igamova Inoya; Igamova Parvina; Bekirova Elzara (Research Parks Publishing LLC, 2020)
In the article, the authors noted the need to use role-playing games in the classroom, since role-playing games develop the spoken language of students, enrich their vocabulary, and also educate the spiritual, cultural and moral qualities of a person.